Modeling of Phosphorous Load and Transport Pathways in Dhidhessa Catchment, Oromiya, Ethiopia - Befekadu Kebede, Adisu; Fufa Feyessa, Fekadu; Takala Dibaba, Wakjira (International Journal of Environment, 2019)
Pollution of surface water with harmful chemicals and eutrophication with excess nutrients are recent serious environmental concerns. This lends the need of knowing the nutrient loading and transport mechanism that will occur with different spatial and temporal extent. Thus, effective information regarding the nutrients load and transport mechanisms are important to hydrologists, water use planners, watershed managers and decision makers for water resource projects and planet ecosystem. Our study aimed for modeling of phosphorous loading and its transport pathways and to identify the most vulnerable sub basin responsible for a significant phosphorus load in Dhidhessa catchment using Soil and Water Assessment Tool (SWAT) model. The pathways of phosphorus were identified and found that the organic phosphorus was dominant exporting mechanism accounted for 58.89% of the total path in the study area. For all forms of phosphorus, surface run off was the most dominant means of transport agent. The average annual loading of total phosphorus was identified as 20 kg ha-1. The sub basins 17, 23, and 3 were identified as the highest loading area of total phosphorous in the study catchment. Best management plan which is simple, economical and adaptable over the study catchment for managing severe impact of surface run off on water resources should be adopted. It is better to undergo detail re-examination over the physical and chemical properties of P in fertilizers and manures to propose the minimizing, neutralizing, replacing strategies to reduce at the source.